Internationalization Process for Micro and Small Software Companies: A Descriptive Study - Bento, Mariani Margarida; Galhardi, Lucas Busatta; de Morais, Janaína Ignácio; Brancher, Jacques Duílio (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2021)
Micro and small companies face different challenges related to entering international markets. Knowledge about these aspects is essential for understanding how to start internationalization activities. This information is present in the literature and in agencies/programs that promote international activities. This article presents a descriptive documentary analysis of the internationalization processes of software companies. To carry out the analysis, scientific articles and internationalization guides were found in the main internationalization incentive programs. The results presented the 5 basic questions about the internationalization process, namely: motivations, products offered, how companies enter the international market, when international expansion takes place, and the main countries of entry according to the literature and guides of internationalization. The organizational characteristics of the companies were identified, the paths followed by the software companies, services and how information is provided by the incentive agencies.